Vitamin D status and supplementation in elite Irish athletes - Magee, P. J.; Pourshahidi, L. K.; Wallace, J. M. W.; Cleary, J.; Conway, J.; Harney, E.; Madigan, S. M. (Research in Sports Medicine, 2013)
A high prevalence of vitamin D insufficiency/deficiency, which may impact on health and training ability, is evident among athletes worldwide. This observational study investigated the vitamin D status of elite Irish athletes and determined the effect of wintertime supplementation on status.